DETERMINACIÓN DE LOS COSTOS DE PRODUCCIÓN EN LA CRIANZA DE TILAPIA ROJA EN LA PISCÍCOLA “PATOCOCHA” DE LA PARROQUIA NAMBACOLA, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA - Jara Armijos., Maritza Ximena (2019)
The thesis work entitled "DETERMINATION OF THE COSTS OF PRODUCTION IN THE RED TILAPIA AGING IN THE PATOCÍCOLA" PATOCOCHA "OF THE NAMBACOLA PARISH, CANTON GONZANAMÁ, PROVINCE OF LOJA", was structured taking into account the data of the production, where each activity carried out and the time invested in the processes was known, due to the great importance that fish production has in the subject served as a support tool, and it was also elaborated to fulfill the prerequisite to choose the degree and title of Engineer in Accounting and Auditing, Auditing Public Accountant, of the National University of Loja. For the fulfillment of the objectives the application of the system of costs by process was made, the same one that was based on the handling of the different methods that were carried out in the production, started with the structure of the inventory through the physical verification of the goods of the fish farm, auxiliary records were designed as: purchase orders, registration of food consumption, order of requisition of materials, transcripts, clock and time cards, worksheets, cost sheet; they were used to record the economic facts that allowed to know the real value of the costs that affect production, therefore establishing the sale price of each pound of red tilapia. In order to reflect the economic facts, a report was 5 made at the end of each process, detailing the units in process, raw materials, labor and indirect production costs. The proper and orderly application of each of the components of the production process of red tilapia, allowed to supply the raw material in correct amounts, for it was necessary to weigh 1% of the population and in this way feed them politely, it was possible to demonstrate that the cost of labor does not vary if the owner produced more than 3000 fish, as well as the indirect production costs. The fish farm "PATOCOCHA" has a large physical space, therefore it is recommended that the owner make use of this tool in which the entire process is detailed taking into account that the results obtained are profitable but must be considered in producing in large quantities to obtain good profitability.